2010
DOI: 10.1002/cncr.24976
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal melanoma of the nose and paranasal sinuses, a contemporary experience from the M. D. Anderson Cancer Center

Abstract: BACKGROUND: Sinonasal mucosal melanoma is a rare disease associated with a very poor prognosis. Because most of the series extend retrospectively several decades, we sought to determine prognostic factors and outcomes with recent treatment modalities. METHODS: A retrospective chart review of 58 patients treated for sinonasal melanoma at a tertiary cancer center between 1993 and 2004. The patients were retrospectively staged according to the sinonasal American Joint Committee on Cancer (AJCC) staging system. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
191
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(213 citation statements)
references
References 30 publications
14
191
1
7
Order By: Relevance
“…Compared to their oral counterpart sinonasal melanoma have lower rate of regional spread and more commonly present as ulcerative or polypoid morphology, pseudopapillary growth pattern with necrosis and a tendency towards perineural invasion. [12] Mucosal melanoma may be suspected from their gross appearance presenting as a large polypoidal and bulky mass which may or may not contain melanin pigment. Microscopically, these tumours usually show lymphoid infiltrate at the periphery which may be due to immune response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to their oral counterpart sinonasal melanoma have lower rate of regional spread and more commonly present as ulcerative or polypoid morphology, pseudopapillary growth pattern with necrosis and a tendency towards perineural invasion. [12] Mucosal melanoma may be suspected from their gross appearance presenting as a large polypoidal and bulky mass which may or may not contain melanin pigment. Microscopically, these tumours usually show lymphoid infiltrate at the periphery which may be due to immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that the presence of mitotic figure (>10/10 HPF) may be associated with worse clinical outcome. [6,12] The differential diagnosis of sinonasal mucosal melanoma may include undifferentiated carcinoma, lymphoma, plasmacytoma, rhabdomyosarcoma and olfactory neuroblastoma. [6] which may not be reliably differentiated on histology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of the data pertains to head and neck mucosal melanomas and the addition of postoperative RT offers a local control benefit. The local recurrence rates with adjuvant radiation ranges from 15 to 30% (27)(28)(29). Despite the local control benefit of adjuvant radiation, there is no impact on overall survival, likely due to the high risk of systemic relapse (28)(29)(30)(31)(32)(33).…”
Section: Rt In Mucosal Melanomasmentioning
confidence: 99%
“…One study has shown that association of targeted therapies and immunotherapy with checkpoint inhibitors appears to show the highest response rates and longest progression-free survival in advanced cases 8 . Despite a better knowledge of this tumor, the 5-year overall survival remains poor, does not exceed 40% in any of the published studies and usually it is diagnosed in an advanced stage of disseminated disease 9 .…”
Section: Introductionmentioning
confidence: 98%